2014
DOI: 10.1167/iovs.13-13792
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Imaging of Photoreceptors in Macular Microholes

Abstract: Cone disruption occurs in eyes with macular microholes and a larger cone disruption area translates into a poorer visual acuity. Macular microholes, which are commonly observed as foveal cone inner and outer segment disruptions, may occur in eyes with or without vitreofoveal traction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…This case also illustrates the subtle abnormality that may persist in the ellipsoid zone after healing of the laser injury. Such a lesion mimics previously described macular microholes . However, increased cone signal within the region of outer retinal lamellar defect has not been described before.…”
supporting
confidence: 82%
“…This case also illustrates the subtle abnormality that may persist in the ellipsoid zone after healing of the laser injury. Such a lesion mimics previously described macular microholes . However, increased cone signal within the region of outer retinal lamellar defect has not been described before.…”
supporting
confidence: 82%
“…4 Various studies have reported that they can occur either with or without vitreomacular tractional interactions. In their study investigating 14 macular microholes, Ooto et al 5 reported that 64% of the eyes (9 eyes) exhibited complete or incomplete PVD, while 36% (5 eyes) showed no signs of PVD or vitreous traction. They suggested the possibility of a primary pathology in this group of microholes that may arise in the photoreceptor layer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cone-rich rim and the foveola differ, and quite significantly, i.e., the photoreceptor outer segments in the cone-rich rim are tiny or absent [ 85 ], while the outer segments of central foveolar cones are approximately twice as long as those of parafoveal cones [ 86 ]. However, ocular coherence tomography (OCT) examination frequently reveals that disruption of the ellipsoid zone is restricted in the foveolar region in various macular diseases, such as a macular microhole, acute retinal pigment epitheliitis, and laser-induced maculopathy [ 87 , 88 , 89 ], and OCT images of these lesions are at least partly regarded as a loss of cone outer segments [ 90 ].…”
Section: Discussionmentioning
confidence: 99%